Semantic Approach for Digital Restoration of Balinese Lontar Manuscripts - Sarasvananda, Ida Bagus Gede; I Gde Eka Dharsika; Saputra, I Wayan Kelvin Widana; Welda, Welda (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2024)
Balinese lontar manuscripts represent a cultural heritage containing significant historical, religious, and scientific values. However, their centuries-old age makes them vulnerable to damage. This research proposes a semantic-based digital restoration solution to address this issue. The semantic approach comprehends the meaning and structure of the lontar text, ensuring an accurate restoration process that preserves the original meaning. The development of the semantic-based digital restoration is built using the Design Science Research Methodology (DSRM). The system is equipped with data management features that accommodate new data, ensure accurate information updates, and maintain the integrity of relationships between entities. Testing through SPARQL query approaches and black-box testing indicates that data additions, deletions, and modifications function well without conflicts or inconsistencies. Moreover, the system performs as expected and is ready for use. The implications of this research suggest that semantic-based digital restoration can be an effective solution for preserving Balinese lontar manuscripts and similar cultural heritage.